The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su132312947
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Environmental Regulations on Industrial Green Total Factor Productivity: Perspectives on the Changes in the Allocation Ratio of Factors among Different Industries

Abstract: This paper constructs a two-sector manufacturer model of endogenous technological progress. We analyze the impact of environmental regulations on the factor input and output of different industries. Then, we reveal the intermediary role of inter-industry factor allocation in the impact of environmental regulations on industrial green total factor productivity (GTFP). Finally, the paper uses panel data from 30 provinces in China’s industry from 2000 to 2017 to conduct empirical tests. We can draw the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The main reason is that, compared with other regions, the Yellow River Basin has special innate natural conditions and acquired social function positioning, and is subject to strong environmental regulations, so the green total factors fluctuate greatly. The conclusion that environmental regulation significantly promotes the growth of GTFP is consistent with most scholars' research, which verifies the establishment of Porter's hypothesis from the perspective of productivity, indicating that pollution control and the improvement of productivity may become a win-win situation [34,35]. However, a considerable number of studies have shown that the high-intensity environmental regulation has an inhibitory effect on industrial GTFP [36,37].…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…The main reason is that, compared with other regions, the Yellow River Basin has special innate natural conditions and acquired social function positioning, and is subject to strong environmental regulations, so the green total factors fluctuate greatly. The conclusion that environmental regulation significantly promotes the growth of GTFP is consistent with most scholars' research, which verifies the establishment of Porter's hypothesis from the perspective of productivity, indicating that pollution control and the improvement of productivity may become a win-win situation [34,35]. However, a considerable number of studies have shown that the high-intensity environmental regulation has an inhibitory effect on industrial GTFP [36,37].…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…They found that the green technological innovation of the province can significantly improve its AGTFP but restrains the neighboring provinces’ AGTFP. Yuan and Zhang [ 13 ] analyzed the impact of environmental regulations on the input and output of production factors and found that environmental regulation has an inverted “U” curve on AGTFP. However, the allocation rate of production factors can reverse the inhibitory effect of strict environmental regulations on agricultural total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, in terms of the validation of classical low carbon taxation theory, the first is the "double dividend" effect, which Yuan and Zhang (2021) argue can be achieved by environmental regulation policies that can lead to economic growth and pollution reduction. From an economic perspective, Cao et al (2021) conduct a multimodel comparison of a carbon tax policy in China and find substantial differences in the change in energy use and economic activity in response to a steadily rising carbon tax.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To avoid affecting the accuracy of the model regression results due to the omission of important variables, based on the practices of Tu et al (2019), Yuan and Zhang (2021) and Yang et al (2022) and combined with the characteristics of the sample data in this paper, local competition (Compete), industrial structure (Ind), the degree of government intervention (Gov), fiscal decentralization (Fd), environmental regulation (Er) and population density (Den) are used as control variables, and the specific definitions of the variables are shown in Table 4.…”
Section: ) Control Variablesmentioning
confidence: 99%